Pengaruh Komunikasi Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan PT Nusantara Surya Sakti Banjarmasin di Masa Pandemi - Muhammad Imam Sidik Permana; Titien Agustina; Lita Nortyana (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
The purpose of this study was to analyze the influence of work communication and the work environment on the performance of employees of PT Nusantara Surya Sakti Banjarmasin which was carried out during the Covid-19 pandemic. The influence test between variables is carried out simultaneously or partially. This research is a type of quantitative descriptive research with data collection methods through questionnaires. Data analysis using multiple linear regression. The results of the study show that work communication and work environment have a simultaneous or partial effect on employee performance during the Covid-19 pandemic. Work communication and work environment simultaneously affect the performance of Nusanrata Surya Sakti Banjarmasin employees by 59.5%. While the partial effect of work communication on employee performance has an effect of 36.3% and the effect of the work environment on employee performance is 24.2%.